A Brief Study of the Essential of Economics - Masuda, Yuji (Modern Perspectives in Economics, Business and Management Vol. 6, 2021)
Understanding money, which is created from bartering, is essential in economics. The purpose of this study was to examine the mechanism of money from a fundamental perspective, and succeeded in describing the structure of modern consumption and even trends in the industrial economy in the coming decades.